(untitled) (Publicaciones en Ciencias y Tecnología, 2021)
The purpose of this work is the basic design of a photovoltaic installation in a residential home in the city of Madrid in two (2) cases, in which the acquisition and use of an electric vehicle is considered or not. The PVGIS® database is used to estimate the irradiation of the area, located between 86 and 233 kWh / m2. Case A considers the consumption of the home and the electric vehicle. Its design consists of 11 photovoltaic modules and seven (7) lithium-ion batteries with their accessories. Case B, which only considers the consumption of the home, consists of eight (8) photovoltaic modules and four (4) lithium-ion batteries, as well as other accessories. The comparison is carried out on the economic profitability of both facilities and the avoided emissions of each of them are determined. It is proven that Case B is more profitable economically, but it is Case A that allows avoiding the greatest amount of greenhouse gas emissions.